Mineral wool primary layer formation in collecting chamber - Bizjan, Benjamin (Strojniški vestnik, 2016)
The process of the mineral wool primary layer formation was investigated experimentally on a model spinning machine with sucrose as a working medium. The fibers were pneumatically transported from the spinner rotor to the accumulation grid with the aid of the blow-away and the suction airflow. The fiber primary layer formed on the accumulation grid was visualized by a camera for several different operating regimes. Acquired images were post-processed to determine the light absorption in the primary layer, which was then used to calculate the bulk density and the surface density of the layer. Based on the measured process quantities, we were able to form multiple regression models with a relatively good correlation to the experimental data. The models as well as the qualitative image analysis show a significant effect of spinner rotor rotational speed, pneumatic transport velocity and fiber deposit mass on primary layer bulk density and spatial distribution of fibers.
Keywords: centrifuga; mineralna volna; pnevmatski transport; primarna plast; vlakna; zbiralna komora